Evaluasi Program Revitalisasi Pasar Banyuasri - Wibawa, Putu Adi Putra; Suwena, Kadek Rai (Jurnal Pendidikan Ekonomi Undiksha, 2025)
This study aims to evaluate the Banyuasri Market revitalisation program in Singaraja City. The evaluation is based on the dimensions of effectiveness, efficiency, relevance, and impact using Cost-Benefit Analysis (CBA) and Cost-Effectiveness Analysis (CEA). The research used a descriptive qualitative approach with data collected through observation, in-depth interviews, and documentation. The results show that the revitalisation program has not been fully effective in improving the competitiveness of traditional markets. Although the infrastructure has improved, traders' income has declined due to a significant increase in operating costs. The program's efficiency is also not optimal, as the investment does not match the economic results. The program's relevance is considered lacking, as it does not consider post-pandemic socioeconomic conditions. The impact of the revitalisation has even caused resistance among traders, mainly due to relocation and rising tariffs. Therefore, further evaluation and policy adjustments are needed so that the market revitalisation can provide optimal benefits for all stakeholders.